A simulation approach for investigating the performances of cadmium telluride solar cells using doping concentrations, carrier lifetimes, thickness of layers, and band gaps. (1st March 2021) - Shah, Deb Kumar; KC, Devendra; Muddassir, M.; Akhtar, M. Shaheer; Kim, Chong Yeal; Yang, O-Bong
Highlights: A simulation study for the optimization of high-performance cadmium telluride (CdTe) solar cells. Doping concentrations, carrier lifetimes, and thicknesses of CdTe/CdS layers are considered. Highest efficiency of 18.29 achieved at doping concentration of 1.5 × 10 17 cm −3 for absorber layer. The efficiency increases with increase in carrier lifetime and thickness of absorber layer. Abstract: This paper describes the simulation study for the optimization of high-performance cadmium telluride (CdTe) solar cells using different doping concentrations, carrier lifetimes, temperature, and thickness of layers of CdTe absorber and CdS window layers. In this simulation, the highest efficiencies of ~18% and ~18.29% achieved when the doping concentrations were 1.5 × 10 17 cm −3 for absorber layer and 1 × 10 15 cm −3 for window layer, respectively. The efficiency of the solar cell increases with increase in carrier lifetime and the highest efficiency of 18.26% achieved at carrier lifetime 100 μs with doping concentration of 1 × 10 17 cm −3 . Solar cell with the thickness of absorber layer 8 μm at carrier lifetime 100 μs attained the maximum efficiency of 19.18% whereas the efficiency of 18.33% was noticed in thickness of window layer 70 nm at 100 μs carrier lifetime. The optimum efficiency of 18.3% with short-circuit current 2.66 A and open-circuit voltage 0.79 V of solar cell has been achieved at operating temperature 25 °C. The optimized energy band gap of absorber (1.7 eV) accomplished the highest efficiency of 18.31%. The photogeneration rate increases logarithmically as distance from front increases, while the recombination rate increases linearly, which could be suitable for fabrication of efficient solar cell.